Cohen, Ed., Dear Mrs. Roosevelt - Letters From Children Of The Great Depression - Merriman, Scott (Teaching History: A Journal of Methods, 2004)
Robert Cohen, in Dear Mrs. Roosevelt, presents an edited collection of letters from youth (children and teenagers alike) written to Eleanor Roosevelt during the Great Depression. The volume opens with a discussion of why these youth wrote to Roosevelt, and it notes how hard the Great Depression impacted children. Cohen includes a discussion in his introduction of what the New Deal did for children, why so many letters were written (he notes that up to 300,000 letters were written to Mrs. Roosevelt annually), and why these letters were written to Eleanor rather than to FDR.